1984
DOI: 10.1007/bf01908299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prostacyclin infusion during low-flow ischaemia in the isolated perfused rat heart

Abstract: Although prostacyclin (PGI2) has been shown to exert a protective effect on ischaemic hearts its precise mode of action remains obscure. Possible explanations include protection of the high energy phosphate stores (ATP and CP), maintenance of homeostasis with respect to Ca2+, and an antiaggregatory effect. The following experiments were undertaken to investigate these possibilities, using isolated, spontaneously beating rat hearts perfused with Krebs-Henseleit solution. Ischaemia was induced at 37 degrees C fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…PGI 2 formed in the blood vessel endothelium is thought to act as an antagonist against TXA 2. Administration of PGI 2 or PGI 2 analog has been reported to have improved the protection against reduced myocardial contractility [21]. In the present study, PGI~ increased significantly during ischemia when LDL was infused.…”
Section: Discussionsupporting
confidence: 54%
“…PGI 2 formed in the blood vessel endothelium is thought to act as an antagonist against TXA 2. Administration of PGI 2 or PGI 2 analog has been reported to have improved the protection against reduced myocardial contractility [21]. In the present study, PGI~ increased significantly during ischemia when LDL was infused.…”
Section: Discussionsupporting
confidence: 54%
“…However, the role of PGI 2 in the protective mechanisms of L-carnitine in the heart has not been determined. PGI 2 has been reported to alleviate myocardial ischemia-reperfusion injury [23,24]. Due to the short half-life of PGI 2 ; therefore, the more stable PGI 2 analogs were developed.…”
Section: Introductionmentioning
confidence: 99%
“…The data from this part of the study indicate that TXAt mimetics may be reducing LDH release because of their ability to induce production of other prostanoids with protective actions. One possibility is prostacyclin which has been shown to have beneficial effects during myo cardial ischemia [27], We showed that pros tacyclin production was increased by U-46619 treatment during ischemia in the buff er-perfused rat heart. As previously pub lished [ 18], we found that ischemia itself also increased prostacyclin production, but U-46619 further increased its production.…”
Section: Discussionmentioning
confidence: 77%